2008
DOI: 10.1007/s10948-008-0374-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Li Substitution in Bi-2223 Superconductors

Abstract: The effects of Li substitution on the properties of high temperature superconductor Bi 17 Pb 0.3 Sr 2 C 2 Cu 3−x Li x O y were investigated. The samples were prepared by substituting Li (x = 0.00-0.20) with changing ratios by a solid state reaction method. The samples were characterized by X-ray diffraction, DC electrical resistivity, AC magnetic susceptibility, and scanning electronic microscopy (SEM). The X-ray diffraction studies were done at room temperature and the lattice constants of the material were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
40
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(45 citation statements)
references
References 16 publications
3
40
0
2
Order By: Relevance
“…Moreover, alkaline metals have a +1 valence state; hence, their substitution is attractive from the point of changing carrier concentration. The effects of substituting alkaline metals for Bi, Sr, and Cu in BSCCO were studied by [39][40][41] and reported that while the Tc was increased by Li and Na doping, it was decreased by K and Rb. It was also found that alkaline metals drastically decreased the formation temperature of the Bi-2212 phase.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, alkaline metals have a +1 valence state; hence, their substitution is attractive from the point of changing carrier concentration. The effects of substituting alkaline metals for Bi, Sr, and Cu in BSCCO were studied by [39][40][41] and reported that while the Tc was increased by Li and Na doping, it was decreased by K and Rb. It was also found that alkaline metals drastically decreased the formation temperature of the Bi-2212 phase.…”
Section: Introductionmentioning
confidence: 99%
“…A recently synthesized new Y-based HTS, Y 3 Ba 5 Cu 8 O 18 (Y358), exhibited superconductivity above 100 K [11]. In the previous studies of our group, several types of substitution studies were also done to improve the desired high-T c phase [12][13][14][15]. Research on doping or substitution of other elements into cuprate superconductors not only contributes to the find of applications for superconductivity but also helps to determine the pairing mechanism in HTSs.…”
Section: Introductionmentioning
confidence: 99%
“…The granular morphology for the un-substituted sample x = 0, consists primly of flaky layers of large platelet-like structure with random alignment distribution as shown in Fig. 2(a), which is a signature of (Bi,Pb)-2223 phase formation [48,49]. The platelet grains are well linked as x increases to 0.025, in which the platelet-like grains still have a flaky structure.…”
Section: Characterization and Investigationmentioning
confidence: 98%